2016
DOI: 10.18632/oncotarget.11591
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus and metformin synergistically inhibit hepatocellular carcinoma cell proliferation and improve long-term survival in patients with HCC related to hepatitis B virus induced cirrhosis after liver transplantation

Abstract: Immunosuppressive agents used postoperatively after liver transplantation (LT) for hepatocellular carcinoma (HCC) favor recurrence and metastasis. Therefore, new effective immunosuppressants are needed. This retrospective study assessed combined sirolimus and metformin on survival of HCC patients after LT. In 2001-2013, 133 HCC patients with LT were divided into four groups: sirolimus and metformin combination (Sir+Met), sirolimus monotherapy (Sir), other immunosuppressants in diabetes mellitus (DM) patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…In line with our observation, metformin treatment was associated with reduced tumour recurrence and improvement of OS in patients who underwent hepatic resection for HCC . Another retrospective study in patients undergoing LT for HCC could show that OS was improved in patients receiving sirolimus and metformin . In a small propensity score matched cohort of 76 patients receiving radiotherapy for HCC, medication with metformin was also associated with a prolonged survival .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In line with our observation, metformin treatment was associated with reduced tumour recurrence and improvement of OS in patients who underwent hepatic resection for HCC . Another retrospective study in patients undergoing LT for HCC could show that OS was improved in patients receiving sirolimus and metformin . In a small propensity score matched cohort of 76 patients receiving radiotherapy for HCC, medication with metformin was also associated with a prolonged survival .…”
Section: Discussionsupporting
confidence: 86%
“…[14][15][16][17] Another retrospective study in patients undergoing LT for HCC could show that OS was improved in patients receiving sirolimus and metformin. 18 In a small propensity score matched cohort of 76 patients receiving radiotherapy for HCC, medication with metformin was also associated with a prolonged survival. 19 Another study showed a favourable outcome for metformin in a cohort of 135 patients treated with RFA for HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings also demonstrate that 1 mM of metformin could significantly reduce mTOR activity induced by albumin. A similar inverse association between AMPK and mTOR pathway was shown in many cell types such as hepatocytes (Shen et al, ), airway smooth muscle cells (Liu, Pan et al, ), and cellular models of cancer (Rios et al, ; White‐Al Habeeb, Garcia, Fleshner, & Bapat, ). Comparably, data from renal injury models further indicate the inhibitory effects of metformin on mTOR pathway.…”
Section: Discussionsupporting
confidence: 56%
“…One further study had an intervention arm containing mTOR‐inhibitors and another experimental anti‐oncogenic agent, and was excluded due to the potential confounding effect. Therefore, 23 studies were included in the quantitative analysis …”
Section: Resultsmentioning
confidence: 99%